Safe Food, Fair Food: Trichinella-specific antibodies in domestic pigs in Central and Eastern Uganda - Roesel, Kristina; Dione, Michel; Grace, Delia; Akol, Joyce; Erume, Joseph; Musewa, Angella; Kungu, Joseph (2024)
Cross-sectional study using different direct and indirect diagnostic methods to detect Trichinella antibodies in live pigs and infectious larvae in pork, complemented by metadata on pork consumption practices. This dataset was produced as part of the implementation of the Smallholder Pig Value Chains Development in Uganda (SPVCD) and Safe Food, Fair Food (SFFF) projects. These projects were working to improve the livelihoods of the poor by reducing the health risks associated with pig-sourced food and by improving nutrition and market access for smallholders.